IDENTIFIKASI KEPRIBADIAN DALAM PENDEKATAN PEMBELAJARAN DENGAN MENERAPKAN METODE CERTAINTY FACTOR - Gortap Lumbantoruan; Mufria J Purba (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2020)
An educator is important to know and understand the personality of a student so that the educational process can take place properly so that it can get maximum results. Because students have different personality types and the personality type of a student shows how students accept the learning material provided by the teacher. In the teaching and learning process, educators who do not understand the personality of students will find it difficult to deliver learning materials that will attract students' interest, which will hamper the knowledge transfer process. In this study, the identification of the personality of students using the certainty factor method and the types of personality analyzed were choleric, melancholic, phlegmatic and sanguinis. Based on the personality traits of each. The goal is to make it easier for educators to find ways to educate according to the personality of students. The results obtained are that by using the certainty factor method, the personality of a student is obtained based on the characteristics of the student with a confidence level of 88.43%.